Anti-proliferative effects of paroxetine alone or in combination with sorafenib in HepG2 cells - Yaprak Donmez Cakil; Zeynep Gunes Ozunal; Damla Gokceoglu Kayali; Ranan Gulhan Aktas; Esra Saglam (Universidade de São Paulo, 2023)
Abstract Hepatocellular carcinoma (HCC) is a common cause of cancer-related death. Sorafenib is the first approved drug for the treatment of advanced HCC. Depression is frequent in cancer patients. Moreover, sorafenib might exert depression as an adverse drug reaction and paroxetine, a selective serotonin reuptake inhibitor, is a recommended pharmacotherapy. This study aimed to investigate the potential synergistic effects of paroxetine and sorafenib on HepG2 cell proliferation and death. Paroxetine and sorafenib were administered to HepG2 cells as single-agents or in combination. Cell viability was determined with XTT cell viability assay. Cellular apoptosis and DNA content were assessed by flow cytometry. The expression of anti-apoptotic Bcl-2 was examined by immunofluorescence confocal microscopy. A lower dose of sorafenib was found to be required to inhibit cell proliferation when in combination with paroxetine. Similarly, the coadministration enhanced cellular apoptosis and resulted in cell cycle arrest. Confocal imaging revealed a remarkably lower cell density and increased expression of Bcl-2 following combined treatment of paroxetine with sorafenib. To our knowledge, this is the first study demonstrating the synergistic effect of paroxetine and sorafenib in HCC and might provide a potentially promising therapeutic strategy.